Low Diastolic Blood Pressure and Cognitive Decline in Korean Elderly People: The Korean Longitudinal Study on Cognitive Aging and Dementia - Lee, Dongyun (Psychiatry Investig, 2020)
OBJECTIVE: Cardiovascular diseases are representative risk factors for the onset of cognitive decline. The purpose of this study was to confirm the relationship between diastolic blood pressure and cognitive function in elderly people in Korea. METHODS: Data from subjects who were enrolled in the prospective Korean Longitudinal Study on Cognitive Aging and Dementia were used in this study. Data from 701 subjects whose diastolic blood pressure range did not change (≤79 mm Hg or ≥80 mm Hg) over 2 years were analyzed. To analyze the differences in cognitive function between the groups at the 2-year follow-up, an analysis of covariance was performed with covariates, which were significantly different between the two groups, and the baseline cognitive function. RESULTS: Significant differences were observed between the two groups, and the mean scores on the constructional praxis (η(2)=0.010) and word list recall tests (η(2)=0.018) in the diastolic blood pressure ≥80 mm Hg group were higher than those in the diastolic blood pressure ≤79 mm Hg group at the 2-year follow-up. CONCLUSION: These results indicate that maintaining a DBP below 79 mm Hg presents a greater risk of cognitive decline in Korean elderly people.